READABILITY OF PHYSICS TEXTBOOKS IN SECONDARY SCHOOLS IN SOKOTO METROPOLIS - Kamar, Y. M.; Mallami, Nuraddeen (Sokoto Educational Review, 2017)
This study investigated the readability of some physics textbooks in use in secondary schools in Sokoto metropolis. Three textbooks namely Senior secondary physics by P.N Okeke, Comprehensive physics for secondary schools by G.N Ezebitiro and Principles of physics by M. Nelkon were selected for the study. Factors affecting readability of science textbooks were examined notably nature of questioning style, pictorial representation, leans and concepts presentation and suggestion for practical activities. Two hundred and seventy students from six secondary schools offering physics were involved in the study. Close Readability Test and Communicational Strategies Evaluation Test were used for collection of data. The finding of the study indicated that two textbooks (i.e. Senior secondary physics and Comprehensive Physics for Secondary Schools) were readable to senior secondary students while one (i.e Principles of Physics) was not readable to any of the levels. The three textbooks satisfied most of the qualities required for a textbook to be readable. It was recommended that readable textbooks should be selected for fruitful achievement in the subject.